A reassessment of the tank battle between 4th Armoured Brigade and Panzerregiment 5 during Operation Crusader in North Africa on 19 November 1941 - Biermann, Andreas (Scientia Militaria - South African Journal of Military Studies, 2021)
Operation Crusader took place in the wide context of an integrated, multi-service theatre-level offensive operation in the Western Desert and the Mediterranean from October 1941 through to January 1942. Seen through this lens, Operation Crusader was simply the Army and the Royal Air Force component of a multi-service theatre-level offensive conducted by Allied forces. The operation ended with an almost complete defeat of the Axis troops, the lifting of the seven-month siege of Tobruk and the retreat of the surviving Axis forces to a position on the border of the colonial provinces of Tripolitania and Cyrenaica, in central Libya. Operation Crusader was the first army-level offensive undertaken by the Allied forces in World War II, lasting from 17 November 1941 to 15 January 1942.355 The aim of Operation Crusader was to trigger a large-scale tank battle with Axis tank forces outside the besieged desert port of Tobruk in Libya, to destroy the Axis armoured forces, and to pave the way to lift the siege of Tobruk, which had been conducted by the Axis forces since April 1941. Operation Crusader was the first step in a set of three operations expected to lead to the clearing of the North African coast from Axis forces and subsequently allow an invasion of Sicily in 1942. The battle was the largest tank offensive conducted by Allied forces in either World War I or World War II until the Second Battle of El Alamein in late October 1942. It was characterised by a number of tank battles between the Axis forces under the command of General der Panzertruppen Erwin Rommel and Allied infantry and armoured forces under Lieutenant-General Alan Cunningham and then Lieutenant-General Neil Ritchie, who fought under the overall direction of General Claude Auchinleck, the Commander-in-Chief Middle East. 356 357 The conduct of the battle showed weaknesses in the doctrine of British armoured forces, but it ultimately ended in a victory for the Allied forces. This article analyses the first clash of British and German tanks during Operation Crusader and provides a new perspective on the performance of an experienced British cruiser tank regiment, which calls into question the overall assessment of how British armour performed during the battle. The re-assessment provided in this article is in particular related to the performance of both sides in the battle and the performance of both sides against their tactical objectives on the day, as well as the comparative losses in tanks. The article covers the first engagement of British 4th Armoured Brigade with German armour during the opening stage of Operation Crusader between 17 and 20 November in which it managed to thwart a German counterattack. Utilising primary documents, such as war diaries, messages and reports, this article provides a new perspective on the established view of the battle that also affects our view of the performance of British armoured units at regimental level during this period of the Desert War. The article presents a reassessment of comparative tank combat performance in the early phase of Operation Crusader by analysing the first engagement between Allied and German armour with a view to correcting misconceptions that have until now clouded the historical record, such as the one expressed in General Auchinleck’s despatch on the period, “But our tanks and anti-tank guns were no match for the German, although they were fought with great gallantry:”.358 It also considers hitherto unused primary evidence to shed new light on the losses in tanks suffered by both sides during the battle, and considers how the opposing forces performed in the context of their operational objectives.